Kajian Hukum Terhadap Aset Perseroan Terbatas (PT) yang diterlantarkan Setelah Dileburkan Ditinjau Dari Prespektif Ekonomi - Decroly Raintama; Amelia. A.A Lambajang (Jurnal Hukum Ekonomi Syariah, 2026)
The merger or consolidation of a Limited Liability Company (Perseroan Terbatas/PT) is a corporate action aimed at improving efficiency and business competitiveness. However, in practice, the merger process often gives rise to legal and economic issues, particularly concerning corporate assets that are unmanaged or neglected after the merger has taken place. This condition has the potential to create legal uncertainty, economic losses, and negative impacts on the interests of creditors, shareholders, and the state. This study aims to analyze the legal framework governing neglected corporate assets after a merger and to examine its economic implications within the context of efficiency, asset value, and the optimization of resource utilization. The research employs a normative legal research method using statutory and conceptual approaches, examining the Limited Liability Company Law, as well as relevant legal doctrines and economic literature. The findings indicate that the existing legal regulations concerning the management and responsibility for post-merger assets have not yet provided optimal legal certainty, thereby potentially leading to economic inefficiency and depreciation of asset value. Therefore, stronger regulatory frameworks and clearer legal accountability are required to ensure the protection of stakeholders’ interests and to promote the productive and sustainable utilization of corporate assets. Keywords: Legal certainty, Limited Liability Company, Neglected assets, Economic perspective.